Beach cleaning costs. (15th April 2020) - Cruz, Cesia J.; Muñoz-Perez, Juan J.; Carrasco-Braganza, Maribel I.; Poullet, Patricio; Lopez-Garcia, Patricia; Contreras, Antonio; Silva, Rodolfo
Abstract: Based on the data collection of manual beach cleaning, this article measures and compares the efficiency and productivity of workers from private and public companies in nine municipalities in the Gulf of Cadiz (southwest Spain) and from the Ministry of the Environment, from 2010 to 2012. Taking into account the characteristics of the beaches, using the Clean Coast Index (CCI) and calculated cleaning parameters, as well as introducing the scientific use of €/kg, gave results which can provide guidelines for management practices that improve efficiency in the collection of litter per worker. In Chipiona the lowest efficiency and production results were found, in the high and middle seasons. La Linea de la Concepción and Chiclana, using public contractors, were the most efficient. Private contractors showed 50% efficiency, with the exception of San Fernando in the high season. In the case of Ministry of Environment (MoE) contractors, these had the highest efficiency in all of the seasons, with the highest degree of cleanliness. Among the results, an average value of 27.6 kg of litter collected per hour was found, per person and an average value of € 1/kg for private and public contractors. The highest litter collection rate, with a "moderately clean" degree of cleanliness, was found for operators working for private contractors in San Fernando. The cleaning costs of some municipalities are much higher than the average. With the adjustment of certain parameters, the methodology presented in this article can be applied to beaches elsewhere. Graphical abstract: Image 1 Highlights: The method can be applied with the adjustment of the costs, teams, beach characteristics and the amount of litter collected. The CCI (degree of cleanliness) was used to assign a value to the beach conditions being cleaned by different workers. The costs and the litter density in the seasons allow the teams associated with a given litter production to be estimated. The proposed management practices were validated with studies where they were implemented, obtaining favorable results. By evaluating the efficiency of workers per season, decision makers are better able to manage cleaning tasks appropriately.